2012
DOI: 10.2151/jmsj.2012-107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tropical Indian Ocean Warming and ENSO on Tropical Cyclone Activity over the Western North Pacific

Abstract: In this study, we have investigated contributions of tropical Indian Ocean (IO) sea surface temperature (SST) warming and El Niño-Southern Oscillation (ENSO) to the interannual variability of tropical cyclone (TC) genesis frequency over the western North Pacific (WNP) between 1948 and 2010 and the involved physical mechanisms. Both ENSO and tropical IO Basin Mode (IOBM) warming are found to play important roles in modulating the WNP TC genesis frequency, but their effects are significantly different.The time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 30 publications
8
55
0
Order By: Relevance
“…1. This agrees well with recent studies (Du et al 2011;Zhan et al 2011a;Tao et al 2012) stating that the WNP TC activity is suppressed in summer following strong El Niño events. However, TCs in October is slightly higher than the climatological mean by 0.9 (Fig.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…1. This agrees well with recent studies (Du et al 2011;Zhan et al 2011a;Tao et al 2012) stating that the WNP TC activity is suppressed in summer following strong El Niño events. However, TCs in October is slightly higher than the climatological mean by 0.9 (Fig.…”
Section: Methodssupporting
confidence: 93%
“…Recent studies have revealed that the TCGF significantly decreases over the WNP in the EDC years (Du et al 2011;Zhan et al 2011a, b;Tao et al 2012). In this study, we focus on the longitudinal evolution of TCGF anomaly over the WNP from July to October under the influences of large-scale circulation and environmental conditions in the EDC mode.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…24.1h). The sea level pressure anomaly was slightly positive over the WNP in August 2014, which is different from that in 1998, when the TIO warming after the strong El Niño (1997) induced strong Kelvin wave propagation into WNP, leading to anomalous high pressure over the WNP (Du et al 2011;Tao et al 2012; Supplemental Fig. S24.6).…”
Section: S122mentioning
confidence: 82%
“…Moreover, the influence of ENSO on the WNP TC activity takes place not only in its peak year but also lingers after the mature phase. Although the suppressed cyclogenesis is observed over the central WNP in the decaying El Niño years [9,10], the slightly enhanced TC genesis in the western WNP could lead to increased landfalling TCs in Vietnam [11]. Furthermore, a robust asymmetry of the duration between the eastern Pacific El Niño and La Niña events [12] affects the evolution of the ENSO cycle when the warm SSTA over the equatorial eastern Pacific has dissipated.…”
Section: Introductionmentioning
confidence: 99%